Maternal age at birth and daughters' subsequent childlessness. Issue 2 (4th December 2017) - Basso, O; Weinberg, C R; D'Aloisio, A A; Sandler, D P
Abstract: STUDY QUESTION: Does maternal age at a daughter's birth predict her subsequent probability of lifelong childlessness? SUMMARY ANSWER: In this study population, women born to older mothers were more likely to be childless. WHAT IS KNOWN ALREADY: Although maternal age at childbearing is increasing in many countries, there is limited evidence on whether being born to older parents may influence offspring fertility. STUDY DESIGN SIZE AND DURATION: This analysis included 43 135 women from the US-based Sister Study, a cohort study of 50 884 sisters of women with breast cancer recruited between 2003 and 2009. PARTICIPANTS/MATERIALS, SETTING, METHODS: Participants had no breast cancer at baseline. Women were included in the analytic sample if they were born between 1930 and 1964 and were at least 44 years old at enrolment. Median age when reproductive history was last ascertained was 63.8 years. We estimated relative risks (RR) and 95% CI of lifelong childlessness as a function of maternal age at birth, using multivariable log-binomial models, including total number of siblings, birth order, socioeconomic indicators of the family of origin, race and birth cohort. We examined the association in different subgroups and in a sibling-matched analysis including 802 sister pairs discordant for childlessness. MAIN RESULTS AND ROLE OF CHANCE: Compared with women born to 20–24-year-old mothers, those born to mothers aged 25–29, 30–34 and ≥35 years were more likely to be childless [RR (95% CI): 1.21 (1.14–1.29), 1.30 (1.22–1.39) and 1.40 (1.31–1.50), respectively]. The association was consistent in strata defined by birth cohort, number of siblings, birth order, and participant's educational level, as well as within sister pairs. Overall, we found weak evidence for an independent contribution of paternal age at birth to the daughter's probability of childlessness. LIMITATIONS REASONS FOR CAUTION: All participants had at least one sister, and all information was self-reported. We had no knowledge of whether childlessness was intentional and found only a modest association between maternal age at birth and self-reported indicators of infertility. Still, the association with childlessness was highly consistent. WIDER IMPLICATIONS OF THE FINDING: Given the widespread tendency to delay childbearing, evaluating the influence of maternal age at birth on offspring fertility is a public health priority. STUDY FUNDING/COMPETING INTERESTS: This research was supported in part by the Intramural Research Programme of the NIH, National Institute of Environmental Health Sciences (Z01-ES044005). The authors report no conflict of interest.